2017
DOI: 10.1155/2017/2454267
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Peritubal Infiltration with Bupivacaine and Morphine on Postoperative Analgesia in Patients Undergoing Percutaneous Nephrolithotomy

Abstract: Objective. We aimed to investigate the effect of peritubal local anesthetic and opioid infiltration on pain scores and analgesic consumption in patients who underwent percutaneous nephrolithotomy. Material and Methods. Patients aged between 18 and 65 years and ASA I-III were included in this double-blind, randomized study. The patients were divided into two groups. All patients underwent spinoepidural anesthesia. 20 mL of 0.25 percent bupivacaine + 5 mg morphine (0.5 mL), in Group P (n = 66), infiltrated the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Karaduman et al . [17] had also compared the effect of PT infiltration with bupivacaine and morphine on postoperative analgesia in patients undergoing PCNL and compared the first analgesic demand between the two groups and demonstrated that it was 4.222 ± 3.44 h and 2.288 ± 1.50 h in the PT group and the control group, respectively, which was similar to our study. However, we did not use morphine in the study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Karaduman et al . [17] had also compared the effect of PT infiltration with bupivacaine and morphine on postoperative analgesia in patients undergoing PCNL and compared the first analgesic demand between the two groups and demonstrated that it was 4.222 ± 3.44 h and 2.288 ± 1.50 h in the PT group and the control group, respectively, which was similar to our study. However, we did not use morphine in the study.…”
Section: Discussionsupporting
confidence: 86%
“…Karaduman et al . [17] compared the effect of PT infiltration with bupivacaine and morphine on postoperative analgesia in patients undergoing PCNL and found the mean VAS score/Dynamic visual analogue scale (DVAS) to be significantly lower in bupivacaine group. Kıraç et al .…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was estimated using the effect size between the unilateral and bilateral hyperbaric buprenorphine for mean Bromage time from the pilot study. 5 The formula used was:…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…The basic objective of unilateral spinal anaesthesia is to limit the nerve block exclusively to the surgery site. So important factors affecting successful unilateral subarachnoid block include baricity and volume of drug, the position of the patient, type of needle and its bevel direction and speed of injection [3][4][5].…”
Section: Introductionmentioning
confidence: 99%